Ensuring the Safety of Hydraulic Structures in Central Asia: A Comparative Perspective - Kholmamatovich, Narzullaev Olim; Toshtemirovich, Kholmuminov Jumanazar; Shamsievich, Baratov Azim; Pazilbekovich, Mamatqulov Rashid; Khamidovich, Khamidov Bakhtiyorjon (Faculty of Law, University of Muhammadiyah Malang, 2026)
This study applies comparative legal and descriptive-analytical methods to analyse 30 interstate treaties (1992-2017), national legislation, and regulatory practice in Kazakhstan and Uzbekistan. The results demonstrate that although some neighbouring nations (Afghanistan and Tajikistan) have not ratified the conventions, they have been incorporated into their national laws. This hampers the effectiveness of emergency preparedness and risk prevention measures. Through the “Regional Hydrosecurity Concept,” which harmonises state competencies with international water law norms, this study offers a novel theoretical framework for hydrosecurity in Central Asia. Furthermore, the report proposes a “Model Law on the Safety of Hydraulic Structures” to standardise emergency response protocols, hazard classifications, and legal nomenclature at the regional level. These two approaches work together to produce a logical legal framework that addresses current sectoral issues. In particular, Uzbekistan's experience is of significant importance in this regard, as outdated hydraulic infrastructure further undermines the effectiveness of hydrosecurity governance. The study’s original scientific contribution lies in formulating a “Regional Hydrosecurity Concept” that harmonises state competences, international water law standards, and basin-level governance. The practical significance of the study lies in strengthening legal coherence and regional cooperation, while contributing to the implementation of UN Sustainable Development Goal 6 (Clean Water and Sanitation).